2010
DOI: 10.1007/s12010-010-9084-z
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Protein Chip to Measure PKCβ Activity

Abstract: Phosphorylation of proteins by kinases plays an important role in regulating cellular processes including melanin production in the skin cells. Protein kinase C β (PKCβ) is known to be involved in phosphorylating tyrosinase, the key enzyme of melanin production, regulating the skin pigmentation process. In melanogenesis, PKCβ activates the tyrosinase by phosphorylation of its two serine residues. In this study, phosphorylation activity by PKCβ was monitored on a protein chip for the screening of depigmenting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Difficulties in applying this strategy to more complex eukaryotes include the availability, maintenance, and use of multiple different cell lines. There has been some success using arrayed-protein chips 10 or bead-immobilized PK 11 to identify PK-clients. Feilner et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Difficulties in applying this strategy to more complex eukaryotes include the availability, maintenance, and use of multiple different cell lines. There has been some success using arrayed-protein chips 10 or bead-immobilized PK 11 to identify PK-clients. Feilner et al .…”
Section: Introductionmentioning
confidence: 99%
“…7 Difficulties in applying this strategy to more complex eukaryotes include the availability, maintenance, and use of multiple different cell lines. There has been some success using arrayed-protein chips 10 or beadimmobilized PK 11 to identify PK-clients. Feilneret al used a chip containing 1690 nonredundant proteins to screen potential clients for two A. thaliana mitogen-activated protein kinases (MAPK).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Using this method, sensitivity was increased by three orders of magnitude compared to other microarray approaches with PKA and leptin-kemptide fusions. Lee et al reported analysis of PKCb substrate specificity by microarrays displaying peptide fusion to immobilised maltose binding protein [73]. Another method is the decoration of streptavidin with biotinylated peptides or phosphopeptides.…”
Section: Chemistry Of Peptide Array Preparationmentioning
confidence: 99%
“…PKC widely exists in animal tissues and cells, is the main mediator of signal transduction pathway, and also plays a role that cannot be underestimated in physiological processes such as cell proliferation and differentiation [ 14 ]. In the melanin metabolism pathway, PKC activates the tyrosinase by phosphorylation of its two serine residues [ 15 ]. Activated PKC is bound to the melanosome membrane, and unactivated PKC is free in the cytoplasm of melanocytes [ 16 ].…”
Section: Introductionmentioning
confidence: 99%